Single shot x-ray diffractometry in SACLA with pulsed magnetic fields up to 16 T - Akihiko Ikeda; Yasuhiro H. Matsuda; Xuguang Zhou; Takeshi Yajima; Yuya Kubota; Kensuke Tono; Makina Yabashi (Physical Review Research, 2020)
Single shot x-ray diffraction (XRD) experiments have been performed with an x-ray free electron laser under pulsed high magnetic fields up to 16 T generated with a nondestructive minicoil. The antiferromagnetic insulator phase in a perovskite manganaite, Pr_{0.6}Ca_{0.4}MnO_{3}, is collapsed at a magnetic field of ≈8 T with an emergence of the ferromagnetic metallic phase, which is observed via the accompanying lattice changes in a series of the single shot XRD. We discussed the feasibility of the single shot XRD experiment under ultrahigh magnetic fields beyond 100 T, which is generated with a portable destructive pulse magnet.